PROBLEMATIKA PELAKSANAAN PROGRAM KAMPUS MENGAJAR ANGKATAN 5 BAGI MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI MAKASSAR: Issues in the Implementation of the Campus Teaching Programme for the 5th Cohort for Students of the Indonesian Language and Literature Education Program at the University of Makassar - Veri, Cristian; Ramly; Usman (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the problems encountered in the implementation of the 5th Teaching Campus programme for students of the Indonesian Language and Literature Education Study Programme at Makassar State University. The focus of the study includes problems in the implementation of literacy and numeracy (AKM Class), library administration and reading corners, technology adaptation, and internal student constraints. This study uses a qualitative method with data sources from students participating in the 5th Teaching Campus. The research data consists of statements or sentences that describe the various obstacles experienced by students in implementing the programme. Data collection techniques were carried out through interviews and questionnaires, while data analysis included data reduction, data presentation, and conclusion drawing stages. The results of the study show that students face various problems, including limited internet access, difficulty understanding AKM Kelas questions and applications, low reading skills among students, minimal awareness among schools of the importance of libraries, a lack of appropriate reading materials, limited space for reading corners, limited technological equipment, and low support from schools. In addition, internal obstacles were also found, such as the incompatibility of majors and placements, long distances, delays in funding, and a lack of attention from field supervisors and mentor teachers.